The Efficacy of Oral Atorvastatin for Skin Toxicity in Breast Cancer Patients Undergoing Radiotherapy: A Randomized, Double-blind, Placebo-controlled Trial - Danesh, Mahmonir; Ghasemi, Arash; Hamzehgardeshi, Zeinab; Charati, Jamshid Yazdani; Hosseinimehr, Seyed Jalal (Current Pharmaceutical Design, 2025)
IntroductionMost Breast Cancer (BC) patients undergoing Radiotherapy (RT) are potentially susceptible to skin toxicity and prone to clinical symptom complaints. This study aimed to investigate the effect of oral Atorvastatin (ATV) administration on skin toxicity in BC patients undergoing RT.MethodsOne hundred BC patients were randomly assigned to oral ATV (40 mg) or placebo tablets two days before beginning the RT until the eighth week of the RT regimen was completed. Radiation-induced dermatitis was classified according to the Radiation Therapy Oncology Group (RTOG) criteria for eight weeks of treatment. In addition, during the eight weeks of RT, the clinical symptoms, such as pain, itching, burning, and sensitivity, were scored by patients in both groups according to the Visual Analogue Scale (VAS).ResultsNinety-four BC patients were analyzed in this study. At the end of the seventh week of RT, the between-group analysis showed a statistically significant reduction of 20.7% in the ATV group (1.693 ± 0.846) compared to the placebo group (1.900 ± 0.986, P = 0.036). However, the comparison of the dermatitis grade in the ATV and placebo groups showed a reduction of 54.5% in the ATV group; this difference was not statistically significant (P = 0.072). The results of VAS regarding the clinical symptoms of patients showed pain, itching, burning, and sensitivity to touch to be clinically decreased in the ATV group compared to the placebo group in the 8 weeks, but these differences were not statistically significant.ConclusionAccording to the results of this clinical study, the oral administration of ATV at a dose of 40 mg during RT regimens can effectively reduce skin RT-induced toxicity and improve the self-report clinical symptoms among BC patients.Clinical Trial Registration NumberIRCT20181005041239N1.
Keywords: skin toxicity